Blockchain-Based Management Information Systems: Benefits and Challenges - Awan Setiawan (Sean Institute, 2024)
Blockchain has gained great attention as a technology capable of providing security, transparency and decentralization in the data management process. This research aims to analyze and identify the advantages and challenges associated with implementing a Management Information System (MIS) based on Blockchain technology. This research uses a qualitative approach with descriptive methods. The research results show that the application of blockchain technology has a positive impact in various sectors, such as Management Information Systems, corporate finance, and the entertainment industry. The use of blockchain increases security, transparency and efficiency of information management, facilitating better decision making. Although challenges such as initial costs and regulatory differences arise, the innovative potential of this technology remains significant. With understanding and efforts to resolve challenges, blockchain implementation in various fields is expected to provide greater benefits in improving operational efficiency and data security.